Mannitol Challenge to Assess Therapy Response in Asthmatic Children: An Interventional Cohort Study - Nikolaos Karantaglis; Fotios Kirvassilis; Elpis Hatziagorou; Antonios Gkantaras; Kalliopi Kontouli; John Tsanakas; Maria Emporiadou (MDPI AG, 2023)
Bronchial provocation tests, such as the mannitol challenge, can be performed to identify and quantify the severity of bronchial hyperresponsiveness in asthmatic patients. Studies of the mannitol challenge as a monitoring tool in asthmatic children are limited. Our primary aim was to compare the bronchial hyperresponsiveness to mannitol in treatment-naive asthmatic children between baseline and three months after receiving the indicated asthma prophylaxis. Twenty-three asthmatic patients aged 4-16 years were analyzed in this prospective cohort study. All subjects underwent the mannitol challenge at baseline and after three months of treatment with budesonide ± formoterol. The difference in the provocative dose of mannitol to induce a 15% drop in FEV1 (PD15) between baseline and follow-up, as well as its association with the presence of exercise-induced or nocturnal asthma symptoms, were evaluated. The PD15 value increased significantly post-treatment (228.5 mg [4.50-458.15]; p = 0.04). Independently of the evaluation time point, the PD15 values were significantly lower in the presence of nocturnal asthma symptoms (490 mg [122-635] vs. 635 mg [635-635]; p = 0.03), whereas there was no association between the PD15 value and the presence of exercise-induced asthma (p = 0.73). These results suggest that bronchial hyperresponsiveness to mannitol may be a potential monitoring tool in the pediatric asthmatic population, reflecting therapy response in children receiving prophylactic treatment.